Dispersion braiding and band knots in plasmonic arrays with broken symmetries - Yin Shixiong; Alù Andrea (Nanophotonics, 2023)
Periodic arrays can support highly nontrivial modal dispersion, stemming from the interplay between localized resonances of the array elements and distributed resonances supported by the lattice. Recently, intentional defects in the periodicity, i.e., broken in situ symmetries, have been attracting significant attention as a powerful degree of freedom for dispersion control. Here we explore highly nontrivial dispersion features in the resonant response of linear arrays of plasmonic particles, including the emergence of braiding and band knots caused by band folding. We show that these phenomena can be achieved within simple dipolar arrays for which we can derive closed-form expressions for the dispersion relation. These phenomena showcase powerful opportunities stemming from broken symmetries for extreme dispersion engineering, with a wide range of applications, from plasma physics to topological wave phenomena. Our theoretical model can also be generalized to higher dimensions to explore higher-order symmetries, e.g., glide symmetry and quasi-periodicity.